Web-Based Interactive Digital Media to Improve Elementary School Students' Literacy - Lesi Anggraini; Yadi (JST (Jurnal Sains dan Teknologi), 2026)
Literacy competence encompasses not only the ability to read and write, but also the capacity to comprehend information and apply knowledge across various life contexts. However, the literacy level of elementary school students remains relatively low, particularly in terms of reading comprehension and writing skills. Therefore, strengthening literacy competence is essential to support students’ understanding and communication abilities. This study aims to develop web-based interactive digital media to enhance students’ literacy skills in Indonesian language learning. The research employs a Research and Development (R&D) approach using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The study involves 30 elementary school students and two Indonesian language teachers as participants. Data were collected through expert validation and practicality tests using questionnaires and were analyzed using descriptive quantitative analysis. The main findings indicate that the development of web-based interactive digital media using the ADDIE model successfully produces a high-quality, valid, and practical product for literacy learning in elementary schools. Based on these findings, it can be concluded that the developed media is both valid and practical in improving students’ literacy skills. Furthermore, the implications of this study reinforce constructivist learning theory, which emphasizes that learning becomes more effective when students are actively engaged in the learning process. Interactive media has proven to support student-centered learning.